2017
DOI: 10.1177/1756283x17725977
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and risk of nonalcoholic fatty liver disease: a meta-analysis

Abstract: Background:Increased physical activity (PA) is a key element in the management of patients with nonalcoholic fatty liver disease (NAFLD); however, its association with NAFLD risk has not been systematically assessed. This meta-analysis of observational studies was to quantify this association with dose–response analysis.Methods:Electronic databases were searched to January 2017 for studies of adults reporting the risk of NAFLD in relation to PA with cohort or case-control designs. Studies that reported sex-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 51 publications
3
29
2
2
Order By: Relevance
“…This insignificant result of habitual exercise on NAFLD might be related to the small sample size of that in each group (shown in Table 1). In addition, when we changed the classification of fatty liver to with versus without, the effect of habitual exercise on decreasing fatty liver was significant (adjusted odds 0.76, 95% confidence interval 0.61-0.95, P = 0.014), which was in concordance with the results of a previous study 40 . The difference between age and different grades of NAFLD was not significant before adjustment by Scheff e's post-hoc test initially shown in Table 1.…”
Section: Discussionsupporting
confidence: 89%
“…This insignificant result of habitual exercise on NAFLD might be related to the small sample size of that in each group (shown in Table 1). In addition, when we changed the classification of fatty liver to with versus without, the effect of habitual exercise on decreasing fatty liver was significant (adjusted odds 0.76, 95% confidence interval 0.61-0.95, P = 0.014), which was in concordance with the results of a previous study 40 . The difference between age and different grades of NAFLD was not significant before adjustment by Scheff e's post-hoc test initially shown in Table 1.…”
Section: Discussionsupporting
confidence: 89%
“…There are some biological mechanisms that may help to explain this inverse association. First, it is suggested that high CRF has a close relationship with increased physical activity , which has been proven to be associated with a reduced risk of type 2 diabetes and can protect against hypertension and nonalcoholic fatty liver disease, which are known as risk factors for type 2 diabetes . Second, CRF reflects one’s capacity to achieve a certain exercise performance standard and is improved following exercise training , whereas the latter favorably increases skeletal muscle mass, improves autonomic function, decreases secretions of pro‐inflammatory cytokines, and modifies the metabolic risk factors for type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…For studies that reported the CRF for a category by ranges, the median CRF level for this category was imputed using the average data of the upper and lower boundaries. When the highest or lowest boundary was open‐ended, the width of this category was assumed to be the same as the adjacent category . To further plot the relationship of CRF with the risk of type 2 diabetes, the restricted cubic spline was used to model the CRF level with three knots at fixed percentiles (10%, 50%, and 90%) of the distribution, and these were combined using a multivariate random‐effects meta‐analysis .…”
Section: Methodsmentioning
confidence: 99%
“…Qiu and colleagues conducted a meta-analysis and observed that the amount of physical activity in men was inversely associated with the risk of NAFLD in a dose-dependent manner [38]. The authors report that 500 MET-minutes/week (approximately 150 minutes/week) of physical activity was associated with an 18% risk reduction of NALFD (RR = 0.82, 95% CI 0.73-0.91).…”
Section: Exercise and Liver Fatmentioning
confidence: 99%